The Roles of lncRNA in Cutaneous Squamous Cell Carcinoma - Wang, Yujia; Sun, Bensen; Wen, Xiang; Hao, Dan; Du, Dan; He, Gu; Jiang, Xian (Frontiers in Oncology, 2020)
Cutaneous squamous cell carcinoma derives from keratinocytes and is the second most common cause of non-melanoma skin cancer. Cutaneous squamous cell carcinoma (cSCC) develops rapidly and is also the leading cause of death in non-melanoma cancers. Lymph node metastasis occurs in 5% of cSCC patients, and some patients may even metastasize to the viscera. Patients with regional lymphatic metastasis or distant metastases have a <20% 10-year survival rate, indicating the substantial challenge in treating advanced and metastatic cSCC. Some lncRNAs have been found to be abnormally overexpressed in many tumor tissues, so that they can be considered as potential new biomarkers or targets that can be used in the diagnosis and treatment of cSCC in the future. In this review, we summarize the role of lncRNA in cutaneous squamous cell carcinoma to make a better understanding of mutations in cSCC and lay the foundation for effective target therapy of cSCC.